Programmed cell death-1 contributes to the establishment and maintenance of HIV-1 latency. (17th July 2018) - Evans, Vanessa A.; van der Sluis, Renée M.; Solomon, Ajantha; Dantanarayana, Ashanti; McNeil, Catriona; Garsia, Roger; Palmer, Sarah; Fromentin, Rémi; Chomont, Nicolas; Sékaly, Rafick-Pierre; Cameron, Paul U.; Lewin, Sharon R.
Abstract : Objective: In HIV-infected individuals on antiretroviral therapy (ART), latent HIV is enriched in CD4 + T cells expressing immune checkpoint molecules, in particular programmed cell death-1 (PD-1). We therefore assessed the effect of blocking PD-1 on latency, both in vitro and in vivo . Methods: HIV latency was established in vitro following coculture of resting CD4 + T cells with myeloid dendritic cells. Expression of PD-1 was quantified by flow cytometry, and latency assessed in sorted PD-1 high and PD-1 low/− nonproliferating CD4 + memory T cells. The role of PD-1 in the establishment of latency was determined by adding anti-PD-1 (pembrolizumab) to cocultures before and after infection. In addition, a single infusion of anti-PD-1 (nivolumab) was administered to an HIV-infected individual on ART with metastatic melanoma, and cell-associated HIV DNA and RNA, and plasma HIV RNA were quantified. Results: HIV latency was significantly enriched in PD-1 high compared with PD-1 low/- nonproliferating, CD4 + memory T cells. Sorting for an additional immune checkpoint molecule, T-cell immunoglobulin domain and mucin domain-3, in combination with PD-1, further enriched for latency. Blocking PD-1 prior to HIV infection, in vitro, resulted in a modest but significant decrease in latently infected cells in all donors ( n  = 6). The administration of anti-PD-1 to an HIV-infected individual on ART resulted in a significant increase in cell-associated HIV RNA in CD4 + T cells, without significant changes in HIV DNA or plasma HIV RNA, consistent with reversal of HIV latency. Conclusion: PD-1 contributes to the establishment and maintenance of HIV latency and should be explored as a target, in combination with other immune checkpoint molecules, to reverse latency. Abstract : Supplemental Digital Content is available in the text